2022
DOI: 10.1155/2022/4075522
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Intrathyroidal Follicular Helper T Cells Varies with the Progression of Graves’ Disease and Hashimoto’s Thyroiditis

Abstract: Objective. Autoimmune thyroid diseases (AITD), mainly Graves’ disease (GD) and Hashimoto’s thyroiditis (HT), are common organ-specific autoimmune diseases characterized by circulating antibodies and lymphocyte infiltration. Follicular helper T (Tfh) cell dysregulation is involved in the development of autoimmune pathologies. We aimed to explore the role of intrathyroidal and circulating Tfh cells in patients with GD and HT. Methods. Ultrasound-guided thyroid fine-needle aspiration (FNA) was conducted in 35 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…They have been shown to be involved in the pathogenesis of many autoimmune diseases because the dysregulation of Tfh cell activity results in the increased production in antibodies against self-antigens. In a study conducted by Cai et al, an increased number in Tfh lymphocytes were found in the thyroid glands of patients with HT, which increased with the progression of the disease [37]. A correlation was also found between the number of these cells in the blood and thyroid and the level of antithyroid antibodies, especially anti-TG antibodies and free triiodothyronine.…”
Section: The Involvement Of Tfh In the Pathogenesis Of Hashimoto's Th...mentioning
confidence: 87%
See 2 more Smart Citations
“…They have been shown to be involved in the pathogenesis of many autoimmune diseases because the dysregulation of Tfh cell activity results in the increased production in antibodies against self-antigens. In a study conducted by Cai et al, an increased number in Tfh lymphocytes were found in the thyroid glands of patients with HT, which increased with the progression of the disease [37]. A correlation was also found between the number of these cells in the blood and thyroid and the level of antithyroid antibodies, especially anti-TG antibodies and free triiodothyronine.…”
Section: The Involvement Of Tfh In the Pathogenesis Of Hashimoto's Th...mentioning
confidence: 87%
“…Patients with chronic lymphocytic thyroiditis also show an increase in the number of Tfh belonging to the CD4+ T cell group, which play an important role in the immune response by producing IL-21 and stimulating B-lymphocyte activity [37]. They have been shown to be involved in the pathogenesis of many autoimmune diseases because the dysregulation of Tfh cell activity results in the increased production in antibodies against self-antigens.…”
Section: The Involvement Of Tfh In the Pathogenesis Of Hashimoto's Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…These researchers hypothesize that the thyroid hormones T3 and T4 may encourage T cell proliferation and the decrease in hormones after treatment correlates to the observed decrease in Tfh cells [ 32 ]. One study, however, had different findings, concluding that there was no significant difference in Tfh cells in the PB and that they did not correlate with thyroid hormone levels [ 57 ].…”
Section: T Cellsmentioning
confidence: 99%
“…IL-21 has been found to be elevated in the serum of GD patients and is strongly correlated with TSAb in untreated patients [ 52 , 59 ]. Tfh cells marked by PD-1 or ICOS are higher in the thyroid tissue than in the PB in GD patients [ 57 ].…”
Section: T Cellsmentioning
confidence: 99%